Electrochemical Methods in Archaeometry, Conservation and Restoration - Doménech-Carbó, Antonio; Doménech-Carbó, María Teresa; Costa, Virginia (Monographs in Electrochemistry, 2009)
Electrochemistry plays an important role in preserving our cultural heritage. For the first time this has been documented in the present volume. Coverage includes both electrochemical processes such as corrosion and electroanalytical techniques allowing to analyse micro- and nanosamples from works of art or archaeological finds. While this volume is primarily aimed at electrochemists and analytical chemists, it also contains relevant information for conservators, restorers, and archaeologists.